Data Set for the Reporting of Carcinomas of the Cervix: Recommendations From the International Collaboration on Cancer Reporting (ICCR). (May 2018) - McCluggage, W. Glenn; Judge, Meagan J.; Alvarado-Cabrero, Isabel; Duggan, Máire A.; Horn, Lars-Christian; Hui, Pei; Ordi, Jaume; Otis, Christopher N.; Park, Kay J.; Plante, Marie; Stewart, Colin J.R.; Wiredu, Edwin K.; et al.
Abstract : A comprehensive pathologic report is essential for optimal patient management, cancer staging and prognostication. In many countries, proforma reports are used but the content of these is variable. The International Collaboration on Cancer Reporting is an alliance formed by the Royal Colleges of Pathologists of Australasia and the United Kingdom, the College of American Pathologists, the Canadian Partnership Against Cancer and the European Society of Pathology, for the purpose of developing standardized, evidence-based reporting data sets for each cancer site. This will reduce the global burden of cancer data set development and reduplication of effort by different international institutions that commission, publish and maintain standardized cancer-reporting data sets. The resultant standardization of cancer-reporting benefits not only those countries directly involved in the collaboration but also others not in a position to develop their own data sets. We describe the development of an evidence-based cancer data set by the International Collaboration on Cancer Reporting expert panel for the reporting of primary cervical carcinomas and present the "required" and "recommended" elements to be included in the pathology report as well as an explanatory commentary. This data set encompasses the International Federation of Obstetricians and Gynaecologists and Union for International Cancer Control staging systems for cervical neoplasms and the updated World Health Organization classification of gynecologic tumors. The data set also addresses controversial issues such as tumor grading and measurement, including measurement of multifocal carcinomas. The widespread implementation of this data set will facilitate consistent and accurate data collection, comparison of epidemiological and pathologic parameters between different populations, facilitate research, and hopefully result in improved patient management.